Comparative study on characterization and wound healing potential of goat (Capra hircus) mesenchymal stem cells derived from fetal origin amniotic fluid and adult bone marrow. (June 2017) - Pratheesh, M.D.; Dubey, Pawan K.; Gade, Nitin E.; Nath, Amar; Sivanarayanan, T.B.; Madhu, D.N.; Somal, Anjali; Baiju, Indu; Sreekumar, T.R.; Gleeja, V.L.; Bhatt, Irfan A.; Chandra, Vikash; et al.
Abstract: Caprine amniotic fluid (cAF) and bone marrow cells (cBM) were isolated, expanded and phenotypically characterized by mesenchymal stem cells (MSCs) specific cell surface markers. Both cell types were compared for multilineage differentiation potential by flow cytometry using specific antibodies against lineage specific markers. Furthermore, in vitro expanded cAF-MSCs showed higher expression of trophic factors viz . VEGF and TGF-β1 as compared to cBM-MSCs. Full-skin thickness excisional wounds created on either side of the dorsal midline (thoracolumbar) of New Zealand White rabbits were randomly assigned to subcutaneous injection of either fetal origin cAF-MSCs (n = 4) or adult cBM-MSCs (n = 4) or sterile PBS (control, n = 4). The rate of wound closure was found faster (p < 0.05) in cAF-MSCs treated wounds as compared with cBM-MSCs and PBS treated wounds especially on 21st day post-skin excision. Histomorphological examination of the healing tissue showed that wound healing was improved (p < 0.05) by greater epithelialization, neovascularization and collagen development in cAF-MSCs as compared to cBM-MSCs and PBS treated wounds. Highlights: Differentiation potential of stem cells derived from AF and BM was similar. Stem cells derived from amniotic fluid had increased expression of VEGF and TGF. Amniotic fluid derived stem cells had demonstrated accelerated wound contraction. AF derived stem cell's treatment had improved the histology of healing wounds.